The use of the Brief Child Abuse Potential Inventory in the general population in Finland - Noora Ellonen; Heidi Rantanen; Sari Lepistö; Mika Helminen; Eija Paavilainen (Taylor & Francis Group, 2019)
Objective: The purpose of this research was to analyze psychometric information in the Brief Child Abuse Potential Inventory (BCAP) in a Finnish general population sample. Design: A self-report survey of parents in a primary health care setting and a hospital setting was used to evaluate the use of the BCAP. Setting: The study population consisted of parents who were visiting one of the following contexts: a primary maternity health care clinic, a child health care clinic, and the maternity outpatient clinic, various pediatric outpatient clinics, the general pediatric ward, the pediatric surgical ward, or the neonatal intensive care unit in a hospital setting. Subjects: The BCAP was given to parents at the 30-34th week of pregnancy, when the child was 5 months old or all parents depending on the context. The BCAP was delivered to 759 parents. The final size of the sample was 453 respondents. Main outcome measure: The BCAP, which consisted of 25 items to screen child abuse potential and nine items for evaluation of respondent validity. Results: The internal consistency of the Abuse Risk Scale was good (.770), and the validity scales worked well. The factor structure mirrors with the original factors structure. Conclusion: The psychometric properties of the BCAP reported in the analysis suggest that the BCAP could be a valid instrument to detect child abuse potential in the general population in Finnish health care settings. However, among Finnish respondents there is very little variation in some parts of the measure, which suggests that further research should assess the validity of the instrument in representative samples. Further analysis is also needed to evaluate the correct classification rate of the BCAP.Key points Identification of families at risk of child maltreatment requires valid tools to recognize risk within the general population, as part of child and family needs and risk assessments in family services. 1. The BCAP is valid, reliable, and useful in bringing parental worries under discussion in child and family services. 2. Results of this study can be used for a more systematic and valid child maltreatment risk assessment for identifying families who need help managing their everyday lives.